High Thyrotropin Is Critical for Cardiac Electrical Remodeling and Arrhythmia Vulnerability in Hypothyroidism - Fernández Ruocco, Julieta (2019)
Background: Hypothyroidism, the most common endocrine disease, induces cardiac electrical remodeling that creates a substrate for ventricular arrhythmias. Recent studies report that high thyrotropin (TSH) levels are related to cardiac electrical abnormalities and increased mortality rates. The aim of the present work was to investigate the direct effects of TSH on the heart and its possible causative role in the increased incidence of arrhythmia in hypothyroidism. Methods: A new rat model of central hypothyroidism (low TSH levels) was created and characterized together with the classical propylthiouracil-induced primary hypothyroidism model (high TSH levels). Electrocardiograms were recorded in vivo, and ionic currents were recorded from isolated ventricular myocytes in vitro by the patch-clamp technique. Protein and mRNA were measured by Western blot and quantitative reverse transcription polymerase chain reaction in rat and human cardiac myocytes. Adult human action potentials were simulated in silico to incorporate the experimentally observed changes. Results: Both primary and central hypothyroidism models increased the L-type Ca2+ current (ICa-L) and decreased the ultra-rapid delayed rectifier K+ current (IKur) densities. However, only primary but not central hypothyroidism showed electrocardiographic repolarization abnormalities and increased ventricular arrhythmia incidence during caffeine/dobutamine challenge. These changes were paralleled by a decrease in the density of the transient outward K+ current (Ito) in cardiomyocytes from animals with primary but not central hypothyroidism. In vitro treatment with TSH for 24 hours enhanced isoproterenol-induced spontaneous activity in control ventricular cells and diminished Ito density in cardiomyocytes from control and central but not primary hypothyroidism animals. In human myocytes, TSH decreased the expression of KCND3 and KCNQ1, Ito, and the delayed rectifier K+ current (IKs) encoding proteins in a protein kinase A–dependent way. Transposing the changes produced by hypothyroidism and TSH to a computer model of human ventricular action potential resulted in enhanced occurrence of early afterdepolarizations and arrhythmia mostly in primary hypothyroidism, especially under b-adrenergic stimulation. Conclusions: The results suggest that suppression of repolarizing K+ currents by TSH underlies most of the electrical remodeling observed in hypothyroidism. This work demonstrates that the activation of the TSHreceptor/protein kinase A pathway in the heart is responsible for the cardiac electrical remodeling and arrhythmia generation seen in hypothyroidism.